Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Higher Order Thinking Skills (HOTS) Pada Materi Bioteknologi di Kelas XII - Sartika, Dea; Manalu, Kartika; Rambe, Riris Nurkholidah (Bioscientist : Jurnal Ilmiah Biologi, 2025)
The purpose of this research is to develop valid, effective, and practical teaching materials in the form of LKPD (Student Worksheet) on biotechnology based on Higher Order Thinking Skills (HOTS) for XII grade students. The method used is Research and Development (R&D) with the ADDIE model (analyze, design, development, implementation, and evaluation).The research started with the analysis stage, which included curriculum analysis and analysis of teacher and student needs. Then, the design stage was conducted to prepare the initial product design. Next, the development stage aimed to produce a feasible LKPD based on HOTS in terms of validity, practicality, and effectiveness. Finally, the implementation stage showed that the developed LKPD was highly practical and effective for use as teaching material. The research results show that (1) The validity of LKPD was obtained from validation sheets, with 100% for media, 88.39% for material, and 72.22% for questions. (2) The practicality of LKPD was obtained from teacher and student response questionnaires, with 100% and 88.85%, respectively. (3) The effectiveness of LKPD was obtained with pretest and posttest, with an n-Gain value of 0.93 and a percentage of 93%. Thus, the LKPD is declared feasible for use.